ORAL FINDINGS IN PATIENTS WITH REPLACED RENAL FUNCTION - a pilot study - Maria Dencheva; Asya Krasteva; Tzvetelina Gueorgieva; Angelina Kisselova (Peytchinski Publishing, 2010)
Theaim of this study was to determine the tongue-coating status (using modern index system), the degree of gingival hyperplasia, to register the observed oral lesions in 30 patients with replaced renal function (hemodialysis and renal transplanted).